Fascioperitoneal graft with T-tube drainage for patching bile duct defects - Akkus, MA; Cifter, C; Ilhan, YS; Erdogan, M; Cetinkaya, Z; Bulbuller, N (Springer Verlag, 1998)
Reconstruction of choledochal wall defects in an experimental dog model by T-tube plus fascioperitoneal graft and an evaluation of the short-term results were the aims of this study. Twelve randomly selected mongrel dogs of both sexes, having an average weight of 22.15+/-1.85 kg, were anaesthetized with ketamine HCI and xylazine and underwent laparatomy. The front wall of choledoch canal were excised with its all layers 0.5 cm in diameter at the dis tal part of the cystic duct junctions. These defects were repaired by using grafts prepared of the same diameter from the dorsal fascias of rectus muscles and peritoneum. T-tubes were introduced into the common ducts on the proximal part of the grafts. One of the animals died in the postoperative period due to evantration. T-tube cholangiograms on the twelfth day did not indicate any extravasation or stricture. Histopathological examination of the graft regions on the sixtieth day revealed that the epithelialization had commenced on the border between the bile epithelium and grafts. Based on these early findings, it was suggested that if supported by further studies it may be thought of as a clinical method.
Keywords: common bile duct defects; graft; repair